Malaysian batik industry contribution analysis using direct and indirect effects of input-output techniques - Mohamad Akhir, Noor Haslina; Ismail, Normaz Wana; Utit, Chakrin (Universiti Malaysia Sarawak, 2018)
The objective of this paper is to examine the economic contribution of batik industry to the Malaysian economy by using the input-output analysis technique. Today, batik industry is known as a successful cottage industry. Throughout the years of its existence, batik industry has contributed to creating jobs for local communities, raise the prestige of country's fashion industry through creative design on fabric, support the development of country’s cultural tourism industry as well as to lead the development of Malaysian craft industries. Despite the success of the industry, it's still developed by small enterprises and even, some of batik firms are categorized as microenterprises. This sense raises the question of the extent to which batik industry contributes to the Malaysian economy. Data on batik making in the Malaysian Input-Output Table 2010 was used to examine the economic contribution of batik industry in terms of direct and indirect effects of input-output techniques. This analysis found that this industry contribute significantly to the Malaysian economy through the advantages of indirect effects that is, how the first-order effects of batik industry give rise to second and higher-order effects to other sectors and also, lead to an additional input required especially import commodities and labor.